2021
DOI: 10.1111/papr.13020
|View full text |Cite
|
Sign up to set email alerts
|

The durability of minimally invasive lumbar decompression procedure in patients with symptomatic lumbar spinal stenosis: Long‐term follow‐up

Abstract: Background: Minimally invasive lumbar decompression (mild ® ) has been shown to be safe and effective for the treatment of lumbar spinal stenosis patients with hypertrophic ligamentum flavum as a contributing factor. This study examines the long-term durability of the mild procedure through 5-year follow-up. Pain relief and opioid medications utilization during 12-month follow-up were also assessed. Methods: All patients diagnosed with lumbar spinal stenosis secondary to ligamentum flavum hypertrophy who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…This rate is consistent with the 5.2% rate reported for an earlier study of the mild treatment at 2-year follow-up [35]. At 5-year follow-up, a reported 12% rate of subsequent surgical decompression indicates a low 2.4% per year rate of surgery after treatment with mild [22]. Conversely, systematic reviews of multiple randomized trials comparing ESIs with placebo injections have concluded that the efficacy of spinal injections is limited and that ESIs do not reduce the rate of subsequent surgery [38].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This rate is consistent with the 5.2% rate reported for an earlier study of the mild treatment at 2-year follow-up [35]. At 5-year follow-up, a reported 12% rate of subsequent surgical decompression indicates a low 2.4% per year rate of surgery after treatment with mild [22]. Conversely, systematic reviews of multiple randomized trials comparing ESIs with placebo injections have concluded that the efficacy of spinal injections is limited and that ESIs do not reduce the rate of subsequent surgery [38].…”
Section: Discussionsupporting
confidence: 89%
“…The mild procedure has been previously described in detail [20]. This treatment has been shown to provide statistically superior efficacy compared with ESIs at follow-up intervals ranging from 6 months to 1 year [21], and strong durability for the relief of LSS symptoms over 5 years [22].…”
mentioning
confidence: 99%
“…Importantly, there were no serious device‐ or procedure‐related adverse events and only 5.6% (8 of 143 patients total) required spinal surgery at the levels of the MILD procedure over the 2‐year follow‐up time period 14 . Mekhail et al reported the incidence of open lumbar decompression surgery at the same levels as the MILD procedure during 5‐year follow‐up was 12% (9 of 75 patients total) 15 . Similarly, when considering Superion, Nunley et al reported that 75% of patients randomized to receive Superion for treatment of lumbar spinal stenosis remained free from reoperation, revision, or supplemental fixation at the treated level at 5 years post‐implant 16 …”
Section: Discussionmentioning
confidence: 99%
“…PILD was developed in 2005 as an alternative for cancer patients considered too high risk for open surgical decompression, and has evolved to label indications for direct decompression at spinal levels L1-S1 for symptomatic LSS with two level 1 RCTs, 61 , 62 several level II prospective controlled studies, 63–66 and a 5-year retrospective longitudinal observational durability study demonstrating statistically significant improvement in pain and mobility. 67 …”
Section: Percutaneous Image-guided Lumbar Decompression (Pild)mentioning
confidence: 99%
“…The study further evaluated opioid use and pain relief, finding that the initial results reported were durable throughout the 5-year period. 67 …”
Section: Percutaneous Image-guided Lumbar Decompression (Pild)mentioning
confidence: 99%